(untitled) (Bangladesh Journal of Nuclear Medicine, 2022)
According to the World Health Organization, the number of malignant melanoma cases increases faster worldwide. Early diagnosed and adequately managed malignant melanoma shows a good prognosis. Rare cases of late metastasis of melanoma after long disease free survival, and their growing incidences are reported. This reported case is about a metastatic malignant melanoma who was apparently disease free for 14 years but showed late recurrence and earned clinical interest. A 60-year-old male patient was referred to PET-CT division of National Institute of Nuclear Medicine & Allied Sciences (NINMAS) for the evaluation of a biopsy proven malignant melanoma in right inguinal region. The patient presented with a newly developed asymptomatic nodule on his right thigh. Relevant past medical history included a completely excised lesion in his left axilla for malignant melanoma. Fine-needle aspiration and cytological analysis report of new lesion showed subcutaneous localization of malignant melanoma. 18F-FDG PET-CT imaging showed hypermetabolic soft tissue density mass in right inguinal region; Histopathology report (HPR) proved malignant lesion. Multiple hypermetabolic lesions were seen intra abdominally involving spleen and pancreas with corresponding hypodense lesions on CT scan. Multiple hypermetabolic enlarged intraabdominal, right axillary and right inguinal lymph nodes are also evident. After 14 years of disease free survival the reported case developed malignant melanoma with distal metastases. Although late metastasis is uncommon however physicians should be aware of any newly developed suspicious lesions and PET-CT can play an important role in workup for detection of metastases from melanoma. Bangladesh J. Nuclear Med. 25(1): 45-47, 2022